2010
DOI: 10.1111/j.1399-5618.2010.00828.x
|View full text |Cite
|
Sign up to set email alerts
|

Valnoctamide as a valproate substitute with low teratogenic potential in mania: a double‐blind, controlled, add‐on clinical trial

Abstract: Valnoctamide could be an important valproate substitute for women of childbearing age with bipolar disorder who may become pregnant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 38 publications
(56 reference statements)
0
56
3
Order By: Relevance
“…Antimanic efficacy has not been demonstrated for allopurinol (level 1 negative),167 eslicarbazepine/licarbazepine (level 2 negative),168 gabapentin (Level 2 negative), lamotrigine (level 1 negative),143 omega‐3 fatty acids (level 1 negative),169 topiramate (level 1 negative),143 valnoctamide (level 2 negative),170, 171 or zonisamide (level 2 negative)172 (Table 13). …”
Section: Acute Management Of Bipolar Maniamentioning
confidence: 99%
“…Antimanic efficacy has not been demonstrated for allopurinol (level 1 negative),167 eslicarbazepine/licarbazepine (level 2 negative),168 gabapentin (Level 2 negative), lamotrigine (level 1 negative),143 omega‐3 fatty acids (level 1 negative),169 topiramate (level 1 negative),143 valnoctamide (level 2 negative),170, 171 or zonisamide (level 2 negative)172 (Table 13). …”
Section: Acute Management Of Bipolar Maniamentioning
confidence: 99%
“…Further confirmation of its safety profile has derived from preclinical and clinical investigations of drug-mediated anti-convulsant and mood-stabilizing actions (Barel et al, 1997;Lindekens et al, 2000;Isoherranen et al, 2003;Winkler et al, 2005;Bersudsky et al, 2010;Kaufmann et al, 2010;Mareš et al, 2013;Modi et al, 2017). VCD is effective at a low-micromolar dose level, a slightly reduced level of efficacy compared with ganciclovir (Ornaghi et al, 2016); nonetheless, we found substantial CMV inhibition in vivo with subcutaneous delivery.…”
Section: Discussionmentioning
confidence: 99%
“…This amount is similar to or less than the dose of existing compounds used to treat CMV in clinical settings; for instance, assuming a 60 kg body weight, ganciclovir can be used from 5 up to 20 mg/kg/d in patients with serious infections (Kotton et al, 2013;Choopong et al, 2016;Genentech USA, 2016). Furthermore, the 5 mg/kg dose of VCD for treating CMV infection is lower than the dose used to attenuate seizures and neuropathic pain in neonatal and adult rodent experiments (Winkler et al, 2005;Kaufmann et al, 2010;Mareš et al, 2013;Shekh-Ahmad et al, 2014) and is less than the 20 mg/kg dose that can be used in humans to treat psychiatric dysfunction (Stepansky, 1960;Goldberg, 1961;Harl, 1964;Bersudsky et al, 2010). Together, these findings suggest that VCD may be able to attenuate CMV in the human brain at doses that should be both effective and tolerable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations